A STRAIGHTFORWARD ANALYTICAL WAY OF EVALUATING THE SINGLE-PHASE INVERTER SPWM FREQUENCY SPECTRUM - Hren, Alenka; Mihalič, Franc (Journal of Energy Technology, 2024)
For a DC-AC converter (inverter), a key element in renewable power supply systems, an output voltage of sinusoidal shape is required to assure a high-quality sustainable energy flow. Thus, through the modulation process, this property must be “incorporated” into the output voltage. This operation incurs some harmonic distortion into the inverter output voltage, which can have an undesired influence on the load. In the single- or three-phase systems (grid-connected, uninterrupted power supply systems (UPS) or motor drives), the high quality Total Harmonic Distortion (THD) factor must be considered; the voltage harmonic content also must be limited. This paper provides a comprehensive spectrum analysis of a three-level output voltage in singlephase inverter. The output voltage is generated by triangular Sinusoidal Pulse-Width Modulation (SPWM) and, by using the Fourier analysis, Bessel functions and trigonometric equality, the high harmonic components are extracted in a straightforward analytical way. Finally, the overmodulation phenomenon is also considered, and the procedure is experimentally validated.